2013
DOI: 10.13171/mjc.2.3.2013.22.01.20
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of N-Deacetylation of Chitin Extracted from Shrimp Shells Collected from Coastal Area of Morocco

Abstract: Chitosan was obtained from the alkaline N-deacetylation of -chitin, derived from shrimp shells (SS) collected from the Moroccan coast. Effects of temperature, NaOH concentration and reaction time on the kinetics of deacetylation were studied. The degree of deacetylation (DD = 75%) was obtained at T = 120 °C and CNaOH = 12N in a single step for 6h. It was found, from FTIR studies, that the removal of acetyl groups from chitin occur very fast for the reaction time t < 180 min and then becomes constant aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 0 publications
2
25
0
2
Order By: Relevance
“…The chitin deacetylation process followed the pseudo-first-order kinetics for all the temperatures studied (25, 80, and 120°C) and at the same alkaline concentration (12 N) [3]. The Table 8 showed that the values decreased as a function of temperature.…”
Section: Determination Of Apparent Rate Constant K and Energetic Actimentioning
confidence: 90%
See 3 more Smart Citations
“…The chitin deacetylation process followed the pseudo-first-order kinetics for all the temperatures studied (25, 80, and 120°C) and at the same alkaline concentration (12 N) [3]. The Table 8 showed that the values decreased as a function of temperature.…”
Section: Determination Of Apparent Rate Constant K and Energetic Actimentioning
confidence: 90%
“…The temperature in this step is a factor that weakens the binding of the acetyl groups and accelerates the deacetylation reaction. Ahlafi and al [3] also found that the DDs increase as the NaOH concentration and temperature increase as the time of reaction increases. These reached a maximum of 63% and 71% for C NaOH = 12 N at T = 80 and 120°C, respectively.…”
Section: Ir Study Of the Effect Of Temperature On The Chitin Deacetylmentioning
confidence: 90%
See 2 more Smart Citations
“…This reaction pathway, when allowed to go to completion (complete de-acetylation) yields up to 98% produce. Chitosan may be further purified by preparation of solutions in acid followed by neutralization and precipitation [11,12].…”
Section: Introductionmentioning
confidence: 99%